Modeling of soil nutrient balances, flows and stocks revealed effects of management on soil fertility in south Ecuadorian smallholder farming systems - Chamba Zaragocin, D. (2015)
Linking nutrient balances and flows to soil nutrient stocks creates a valuable indicator for sustainability assessment in agricultural land-use systems. Therefore, we investigated the impact of management on soil fertility at farm/field scale using the Nutmon approach. A detailed methodology for the adaptation of the difficult-to-quantify flows to the local conditions is described. Research was carried out in the three farming systems of Yantzaza (low-external-input), El Tambo (irrigated cash crops) and San Lucas (integrated nutrient management) in southern Ecuador. For each land-use within a farm (annual and perennial crops, pasture, forest), soil nutrient balances and flows were modeled with Nutmon and soil nutrient stocks were calculated for NPK. Soil nutrient balances were evaluated using potential socio-economic and soil fertility explanatory variables. Balances for the different land-uses in the three research areas varied between ?151 to 66 kg ha?1 a?1 for N, ?4 to 33 kg ha?1 a?1 for P and ?346 to 39 kg ha?1 a?1 for K and were mainly negative. Up to 70 % of the balances variability was explained by soil fertility variables and financial flows. Highest external inputs existed in land-uses with a strong market orientation. Land-uses benefiting from a surplus of within-farm flows had the highest soil nutrient stocks. The focus on N fertilization induced highly negative PK balances in annual crops of El Tambo. In contrast, the application of organic fertilizers and nutrient recycling in San Lucas resulted in positive NP balances particularly for perennial crops. NP balances in annual crops of Yantzaza were most negative due to nonexistent fertilization, leaching and burning of crop residues. A non-sustainable land-use of annual crops in Yantzaza was illustrated by total N stock decreases of 4.9 % a?1 and decreased soil organic carbon stocks to 85 % of adjacent forest sites. Results indicated a potential risk regarding sustainable management of soils in the research area and provide a basis for policy and decision makers to develop appropriate management strategies.